Orthodontic Treatment For Class I Malocclusion With Anterior Crossbite And Mild Crowding: A Case Report - Paramma, Zilal I (Journal of Case Reports in Dental Medicine, 2021)
Objective: The aim of this treatment were correcting crossbite with fixed orthodontic appliance by sequence wire. for correction anterior maxillary crossbite and correction maxillary and mandibula crowding, correction overbite and overjet, correction shifting mandibula midline. Methods: Initial treatment with fixed orthodontic appliance by leveling and alignment using niti round wire. Then followed expantion arch of maxillary with Australian wire and stopped in first molar. In mandibula followed using stainless steel wire and keeping not flaring. Addition elastic maxillary up n low for correction openbite caninus and correction interdigitation.Result: crossbite and crowding anterior were corrected, relation of caninus class 1 angle, overjet and overbite is normal, shifting mandibula midline was corrected. Facial esthetic was better.Conclusion: Orthodonti treatment with simple technique without extraction can achieved significant change by using some wire in fixed orthodontic appliance for correction anterior crossbite.